Hadist Pentingnya Menuntut Ilmu: Motivasi dan Manfaatnya - Rahma Nanda Nur Azizah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This study explores the virtues of seeking knowledge in Islam, focusing on the spiritual and moral benefits that accrue from it. Seeking knowledge is considered an essential obligation in Islam, as it provides the right guidance for living according to religious teachings. Knowledge not only offers worldly benefits but also elevates one's status in the eyes of Allah and within society. It is also considered the legacy of the prophets, which must be preserved and practiced by Muslims. Based on Islamic literature and teachings, this study emphasizes that knowledge is a primary path to achieving true happiness in this world and the hereafter. In conclusion, seeking knowledge is a highly noble deed that brings long-term benefits both individually and collectively in the Muslim community.